Comparison of the Effectiveness of Acceptance and Commitment Therapy Group vs. Pharmacotherapy on Quality of Life in Parkinson's Patients - Javidtash, Zahra; Amini, Naser; Baghooli, Hossein; Barzegar, Majid; Ostovan, Vahid Reza (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The present study aimed to determine the difference in the effectiveness of Acceptance and Commitment Therapy (ACT) group treatment versus pharmacotherapy on the quality of life among Parkinson's patients attending the Imam Reza Clinic, Neurology Department, in Shiraz. Methodology: In this quasi-experimental study, 36 participants were purposefully selected and divided into two groups (each group = 18 participants). The tool used for assessment and diagnosis of disorders by the clinical specialist for sample selection was the Parkinson’s Disease Quality of Life Questionnaire. Findings: The findings confirmed the effectiveness of both ACT group therapy and pharmacotherapy on quality of life components, including mobility, activities of daily living, sleep/fatigue, emotional well-being, stigma, social support, cognitive problems/hallucinations, cognition, communication, bodily discomfort, gastrointestinal issues, mobility, activities of daily living, emotional well-being, and sexual function (P